A Case Report on Right Lower Motor Neuron Seventh Cranial Nerve Palsy - Siyad, Anees Sefrin; Rajendran, Aparna Jayadevi; Thomas, Zachariah; Prakash, Remya (Indian Journal of Pharmacy Practice)
Idiopathic facial nerve paralysis or Bell’s palsy is a non-progressive neurological disorder that leads to temporary facial paralysis involving the damage or trauma to the seventh cranial nerve. It can occur due to the exposure to herpes zoster virus or/and immune disorders. Both left and right side may get equally affected and can be complete or partial. Symptoms include poor eyelid closure, dry eyes, alteration of taste, ear pain and increased sensitivity to sound, hemi facial spasm, mass movement contraction and gustatory lacrimation. Treatment with glucocorticoids increases the chance of complete recovery of facial function. Bell’s palsy may leave the surface of the eye exposed, so early eye protection with lubricants and patches are needed to prevent the long-term complications.This case discusses Bell’s palsy in a 59-year-old female patient referred to neurology department with the symptoms of facial deviation on right side, onset of blurred vision and difficulty in walking/unsteadiness while walking. She had a history of type II diabetes mellitus and dyslipidemia. MRI showed no acute infarct and no obvious abnormality in the brain parenchyma thus ruling out the chance of posterior circulation stroke. The symptoms showed by the patient were classical to Bell’s palsy thus confirming the same as diagnosis. She was discharged with oral steroid, eye protectants, vitamin and an antiplatelet.
Keywords: Bell’s palsy; Idiopathic facial nerve; Hemi facial spasm; Gustatory lacrimation; Electromagnetic Resonance Imaging; Corticosteroid drug.